Ink and Intent: Questioned Document Examination and Handwriting Analysis in the Modern Era - Hephzibah Rebeca Babu (AG Volumes, 2026)
Questioned document examination (QDE) is a crucial area of forensic science that utilizes scientific knowledge and sophisticated analytical methods to establish the authenticity, authorship and integrity of a questioned document. This review “Ink and Intent: Questioned Document Examination and Handwriting Analysis in the Modern Era” provides a basic introduction to the principles of handwriting identification and the various aspects of individuality, natural variation, specimen collection, handwriting characteristics and common forgery methods. It also investigates the current scientific and instrumental methods, including microscopy, Video Spectral Comparator (VSC), Electrostatic Detection Apparatus (ESDA), Raman spectroscopy, FTIR, XRF, chromatography and mass spectrometry, for the authentication of documents and the characterization of materials. The review also addresses the effect of Artificial Intelligence, Machine Learning, Deep Learning and Digital Forensic Technologies in Handwriting Comparison, Signature Verification and Digital Document Analysis. Lastly, it underscores the various forensic uses, evidential value, and growing challenges with sophisticated document forgeries and AI-generated documents, while urging for uniform approaches and ongoing technological development to ensure reliable forensic evidence in today’s judicial systems.